THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, PERCEIVED ORGANIZATIONAL SUPPORT, PERSON-JOB FIT, AND TECHNOLOGY ACCEPTANCE ON EMPLOYEE PERFORMANCE MEDIATED BY REMUNERATION (STUDY ON NATIONAL PRIVATE BANKS IN WEST JAVA) - Puti Harissa Pratidhina; Bahtiar Usman; Deasy Aseanty (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyze the influence of transformational leadership, perceived organizational support, person-job fit, and technology acceptance on employee performance mediated by remuneration at National Private Banks in West Java. The study applies a quantitative approach using a survey method. Data collection is cross-sectional with questionnaires distributed to 300 employees of National Private Bank Book 3 in West Java. Structural Equation Modeling (SEM) analysis using AMOS was applied to the collected data. The novelty of this study lies in the addition of remuneration as a mediating variable. The study found that transformational leadership, perceived organizational support, person-job fit, and technology acceptance influence remuneration. Transformational leadership, perceived organizational support, person-job fit, and technology acceptance influence employee performance, and remuneration mediates the influence of transformational leadership, perceived organizational support, person-job fit, and technology acceptance on employee performance. Management should design a remuneration system that is transparent, performance-based, and capable of providing adequate rewards commensurate with employees' contributions and work achievements. This system should integrate balanced financial and non-financial aspects.